Kreativitas Terkomodifikasi: Peran AI dalam Produksi Media Visual pada Media Mainstream - Herlambang Jati Kusumo; Anggi Arif Fudin Setiadi (Jurnal Ilmu Komunikasi, 2026)
The rapid development of Artificial Intelligence (AI) has significantly transformed media production practices, particularly in visual journalism. AI is no longer merely a technical support tool but has begun to participate in creative processes that were previously dominated by human labor. This study aims to examine the implementation of AI in visual media production at Radar Jogja and to analyze how these practices reflect the phenomenon of commodified creativity within the framework of the political economy of media. This research employs a qualitative approach using a case study design. Data were collected through in-depth interviews with editors, social media analysts, and graphic designers, direct observation in the newsroom, and analysis of visual documents and content. The findings indicate that AI adoption is adaptive and produces a hybrid form of creativity that combines human skills with technological automation. AI is primarily used to enhance efficiency, accelerate visual production, and optimize social media content. However, editorial control, ethical judgment, and key creative decisions remain under human authority. The study reveals that visual creativity is increasingly shaped by digital market logic and algorithms, indicating a process of creativity commodification without fully eliminating human creativity.